2019
DOI: 10.1021/acs.jmedchem.9b00039
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pyrazolo[4,3-d]pyrimidine as Potent and Orally Active Inducible Nitric Oxide Synthase (iNOS) Dimerization Inhibitor with Efficacy in Rheumatoid Arthritis Mouse Model

Abstract: In order to discover novel anti-inflammatory agents for treatment of arthritis and based on preliminary structure−activity relationships, four series (A−D) of total 90 new pyrazolo [4,3-d]pyrimidine compounds were designed and synthesized. All the compounds have been tested for their anti-inflammatory activities by inhibiting of LPS-induced NO production. A clear structure−activity relationship has been concluded step by step, and finally 3,4,5-trimethoxystyryl-1H-pyrazolo[4,3-d]pyrimidine was found to be the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Nitric oxide (NO) is produced by mammalian cells through metabolism of l -arginine and plays an important role in regulating inflammation and immune responses 13 . NO is a key pro-inflammatory mediator and excessive production of NO was proved to be associated with many inflammatory diseases 12 , 14 . Thus, it is an established view that compounds inhibiting the production of NO may offer potential opportunity to treat inflammatory diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Nitric oxide (NO) is produced by mammalian cells through metabolism of l -arginine and plays an important role in regulating inflammation and immune responses 13 . NO is a key pro-inflammatory mediator and excessive production of NO was proved to be associated with many inflammatory diseases 12 , 14 . Thus, it is an established view that compounds inhibiting the production of NO may offer potential opportunity to treat inflammatory diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Considering again the contribution of 3,4,5‐trimethoxyphenyl moiety to anti‐inflammatory activity, a fourth series of compounds 218 was designed and synthesized by introducing a trimethoxystyryl group at C‐5 of pyrazolo[4,3‐ d ]pyrimidine nucleus. Out of this series, the compound having propyl‐2‐amine group at R 1 218 significantly inhibited NO (90.4% at 10 µM concentration), iNOS (IC 50 1.12 µM), and iNOS dimerization …”
Section: Synthetic Inos Inhibitorsmentioning
confidence: 98%
“…3,4,5‐Trimethoxyphenyl moiety is another important structural component for anti‐inflammatory potential of molecules . Based on this know‐how, Shi et al designed and synthesized a series of 3,4,5‐trimethoxyphenyl‐pyrazolo[4,3‐ d ]pyrimidine analogs 215 as anti‐inflammatory agents and iNOS inhibitors. However, these derivatives did not display any significant activity.…”
Section: Synthetic Inos Inhibitorsmentioning
confidence: 99%
“…The results revealed that the administration of the compound (125) caused a noteworthy suppression to hind paw swelling on day 30, which was comparable to the effect noticed in the aspirinexposed group. 118 The potency of the selected pyrimidine derivatives versus inammatory mediator (NO) is provided in Table SI…”
Section: Inhibition Of Nitric Oxide (No) Generationmentioning
confidence: 99%